Issues in Transliterating Malayalam Text to Braille - Salah C.and A. Ranjith Ram (International Journal of Engineering Research & Technology, 2015)
Braille is a tactic writing system that has been used by blind. This paper presents a brief survey of character recognition and transliteration works on Braille system and some issues in transliterating Malayalam text to Braille so as to design a system that will transliterate Malayalam scanned books and magazines in to Braille. The proposed system deals with a printed Malayalam text to Braille transliteration system. The system includes a Malayalam optical character recognition system (OCR) and a Malayalam to Braille mapping system.